Right Gastroepiploic Artery as an Alternative for Arterial Reconstruction in Living Donor Liver Transplantation - Klaus Steinbrück; Reinaldo Fernandes; Marcelo Enne; Rafael Vasconcelos; Giuliano Bento; Gustavo Stoduto; Thomas Auel; Lúcio Filgueiras Pacheco-Moreira (Case Reports in Hepatology)
Background. An adequate blood flow is directly related to graft survival in living donor liver transplantation. However, in some cases, unfavorable conditions prevent the use of the hepatic artery for arterial reconstruction. Herein, we report a case in which the recipient right gastroepiploic artery was used as an option for arterial reconstruction in adult-to-adult living donor liver transplantation. Case Report. A 62-year-old woman, with cirrhosis due to hepatitis B associated with hepatocellular carcinoma, was submitted to living donor liver transplantation. During surgery, thrombosis of the hepatic artery with intimal dissection until the celiac trunk was observed, which precluded its use in arterial reconstruction. We decided to use the right gastroepiploic artery for arterial revascularization of the liver graft. Despite the discrepancy in size between donor hepatic artery and recipient right gastroepiploic artery, anastomosis was performed successfully. Conclusions. The use of the right gastroepiploic artery as an alternative for arterial revascularization of the liver graft in living donor liver transplantation should always be considered when the hepatic artery of the recipient cannot be used. For performing this type of procedure, familiarity with microsurgical techniques by the surgical team is necessary.